2020
DOI: 10.12659/ajcr.925932
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Fulminant Liver Failure in a 24-Year-Old Man with Coinfection with Hepatitis B Virus and SARS-CoV-2

Abstract: Patient: Male, 24-year-old Final Diagnosis: Acute kidney injury • coagulopathy • liver failure • SARS-CoV-2 Symptoms: Cough • fever Medication: — Clinical Procedure: — Specialty: Gastroenterology and Hepatology • Infectious Diseases Objective: Unusual clinical course Background: Coronavirus disease 2019 (COVID-19) is a newly emerging disease that is still not fully characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 16 publications
(22 reference statements)
0
19
0
Order By: Relevance
“…Of the five ALF cases reported, three were from the USA and one from Germany and Qatar each. [43][44][45][46][47] Two of these were young, aged 24 years and 35 years, while the other three were above 50 years of age. Most of these patients were critically ill and a single etiology could not be identified as a cause except in the patient with hepatitis B co-infection, who had acute fulminant hepatitis B infection but only mild COVID-19 pneumonia.…”
Section: Sars-cov-2 and Acute Liver Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Of the five ALF cases reported, three were from the USA and one from Germany and Qatar each. [43][44][45][46][47] Two of these were young, aged 24 years and 35 years, while the other three were above 50 years of age. Most of these patients were critically ill and a single etiology could not be identified as a cause except in the patient with hepatitis B co-infection, who had acute fulminant hepatitis B infection but only mild COVID-19 pneumonia.…”
Section: Sars-cov-2 and Acute Liver Failurementioning
confidence: 99%
“…There is a single case report of HBV induced ALF in a patient with mild SARS-CoV-2 infection. 47 …”
Section: Liver Manifestations Of Covid-19mentioning
confidence: 99%
“…There are citations of unique co-infections of SARS-CoV-2 with other systemic viral illnesses [101][102][103][104][105][106][107][108][109][110][111]. Such coinfection was particularly of interest in the context of chronic HIV infection where persistent immunocompromise or enhanced infection susceptibility otherwise might allow for either of the infections to be more severe than not [104][105][106]112].…”
Section: Co-detection Of Sars-cov-2 With Selected Non-viral Infections and Chronic Viral Infectionsmentioning
confidence: 99%
“…These studies do not, however, indicate that either of the latter infections markedly affects the other. For chronic hepatitis B patients, early reports suggest that COVID-19 increases the potential for complicating outcomes [107,108]. Others have suggested that chronic hepatitis B did not predispose patients to a more severe outcome [109].…”
Section: Co-detection Of Sars-cov-2 With Selected Non-viral Infections and Chronic Viral Infectionsmentioning
confidence: 99%
“…Daily, we are witnessing different presentations of the disease. Unusual presentations have been reported in association with COVID‐19 infection, symptoms overlapping with malaria infection, 2 overlapping with HELLP syndrome, 3 seasonal illnesses like dengue fever, 4 liver failure, 5 and precipitating diabetic ketoacidosis (DKA) 6 . DKA is due to insulin deficiency, causing a counter‐regulatory mechanism to break down fatty acids, increasing the production of ketone bodies.…”
Section: Introductionmentioning
confidence: 99%